The Manufacture of Lele Dumbo (Clarias Gariepinus) Feed by Utilizing Industrial Waste of Fish, Cassava and Paddy - Winda Amilia; Andrew Setiawan Rusdianto; Intan Rohmatul Maulidiah; Tommy Eka Chandra Firmansyah (Newinera Publisher, 2020)
A feed is one of the components that supports a cultivation business activity, fish feed must have good nutrition, especially a source of protein. Sources of protein for fish feed ingredients are generally imported, such as peanut meal and fish meal. Utilization of fishery and industrial waste as fish clothing is an effort to overcome the relatively high cost of feed. This study aims to determine the effect of adding formulations on the chemical properties of industrial waste-based catfish feed. The results showed that the more fish meal formulations that were added could increase the protein content in a range of 22.90% -39.90%, fat 5% -7.70%, and ash 5.79% -11.36%. The carbohydrate content decreased with a value range of 33.87% -57.08% and water 7.14% -12%. Fish feed formulations that are close to the SNI for catfish feed are found in treatment P1 with 39.90% protein content test results; water 7,18%; fat 7,7%; Ash 11.36% and carbohydrates 33.87%.